2016
DOI: 10.2989/1814232x.2016.1224205
|View full text |Cite
|
Sign up to set email alerts
|

Otolith shape as a valuable tool to evaluate the stock structure of swordfishXiphias gladiusin the Indian Ocean

Abstract: Swordfish Xiphias gladius is an oceanic-pelagic species. Its population structure in the Western Indian Ocean was studied from the shape of the sagittal otoliths of 391 individuals collected from 2009 to 2014. Normalised elliptical Fourier descriptors (EFDs) were extracted automatically using TNPC software. Principal components analysis (PCA) conducted on EFDs showed no significant effect of side (i.e. left or right otolith). Consequently, all 391 sagittal otoliths were used to identify stocks among six geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
0
13
0
2
Order By: Relevance
“…Coryphaena hippurus (Duarte-Neto et al, 2008), Xiphias gladius (Mahé et al, 2016), Scomber scombrus (Castonguay et al, 1991), and Lutjanus kasmira (Vignon and Morat, 2010). Although these studies tested for DA in roundfishes (and sometimes detected), they never studied it in detail.…”
Section: Directional Bilateral Asymmetry In Otolith Shapementioning
confidence: 99%
See 1 more Smart Citation
“…Coryphaena hippurus (Duarte-Neto et al, 2008), Xiphias gladius (Mahé et al, 2016), Scomber scombrus (Castonguay et al, 1991), and Lutjanus kasmira (Vignon and Morat, 2010). Although these studies tested for DA in roundfishes (and sometimes detected), they never studied it in detail.…”
Section: Directional Bilateral Asymmetry In Otolith Shapementioning
confidence: 99%
“…However, the Elliptical Fourier Analysis (EFA) remains the most widely used method to describe otolith shape. In recent years, the number of studies using EFA has increased substantially and allowed the analysis of population structure of as diverse species as highly migratory oceanic swordfish (Xiphias gladius, Mahé et al, 2016) and sedentary big-scale sand smelt (Atherina boyeri; Boudinar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, study of the morphological characteristics of otoliths, in particular their shape, length, width, area, thickness and weight, has been used to test both genetic and environmental stressors and as a bioindicator to test the differentiation of populations and the variance in stock discrimination studies using Elliptical Fourier analysis (EFA) (Valentine et al, 1973;Campana & Casselman, 1993;Begg & Waldman, 1999;Torres et al, 2000;Smith et al, 2002;Panfili et al, 2005;Turan, 2006;Jawad et al, 2010Jawad et al, , 2011Jawad et al, , 2012aJawad et al, , 2012bJawad et al, , 2012cJawad et al, , 2016Jawad et al, , 2020Vignon & Morat, 2010;Cañás et al, 2012;Jawad, 2012Jawad, , 2013Lord et al, 2012;Treinen-Crespo et al, 2012;Mahe et al, 2014;Trojette et al, 2014Trojette et al, , 2015Abu El-Regal et al, 2016;Brophy et al, 2016;Hüssy et al, 2016;Rebaya et al, 2016Rebaya et al, , 2017Al-Busaidi et al, 2017;Fatnassi et al, 2017;Ider et al, 2017;Khedher et al, 2017;Rodgveller et al, 2017;Chakour & Elouizgani, 2018;Khemiri et al, 2018;Kontaş et al, 2018;Mejri et al, 2018;Wang et al, 2018;…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, study of the morphological characteristics of otoliths, in particular their shape, length, width, area, thickness and weight, has been used to test both genetic and environmental stressors and as a bioindicator to test the differentiation of populations and the variance in stock discrimination studies using Elliptical Fourier analysis (EFA) (Valentine et al ., 1973; Campana & Casselman, 1993; Begg & Waldman, 1999; Torres et al ., 2000; Smith et al ., 2002; Panfili et al ., 2005; Turan, 2006; Jawad et al ., 2010, 2011, 2012 a , 2012 b , 2012 c , 2016, 2020; Vignon & Morat, 2010; Cañás et al ., 2012; Jawad, 2012, 2013; Lord et al ., 2012; Treinen-Crespo et al ., 2012; Mahe et al ., 2014; Trojette et al ., 2014, 2015; Abu El-Regal et al ., 2016; Brophy et al ., 2016; Hüssy et al ., 2016; Rebaya et al ., 2016, 2017; Al-Busaidi et al ., 2017; Fatnassi et al ., 2017; Ider et al ., 2017; Khedher et al ., 2017; Rodgveller et al ., 2017; Chakour & Elouizgani, 2018; Khemiri et al ., 2018; Kontaş et al ., 2018; Mejri et al ., 2018; 2020; Wang et al ., 2018; Ben Mohamed et al ., 2019; Fashandi et al ., 2019; Jmil et al ., 2019; Mahé et al ., 2019; Puentes et al ., 2019; Osman et al ., 2020). Indeed, these studies have shown that the otolith shape is species-specific (Sadighzadeh et al ., 2014) and that variability in the otolith shape, structure and development is influenced by ontogenetic, genetic and environmental factors (Campana & Casselman, 1993; Cardinale et al ., 2004; Vignon & Morat, 2010; Vignon, 2015; Hüssy et al ., 2016; Ider et al ., 2017; Fashandi et al ., 2019), as well as by sex, growth, maturity and pattern of fishery exploitation (Begg & Brown, 2000), or by individual characteristics, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Setidaknya terdapat 5 stok ikan pedang di dunia: Atlantik Utara, Atlantik Selatan, Laut Mediterania, Pasifik, dan Samudera Hindia (Chow et al, 1997). Walaupun terdapat dugaan adanya stok yang terpisah antara sebelah barat dan sebelah timur Samudera Hindia, akan tetapi berdasarkan studi genetik dan otolith, ikan pedang di Samudera Hindia merupakan stok tunggal (Mahe et al, 2014). Stabilitas nilai rata-rata panjang ikan pedang yang tertangkap mengindikasikan bahwa area Samudera Hindia sebelah timur diduga merupakan satu kohort yang didominasi oleh ukuran 170 -175 cm (LJFL), dimana ukuran tersebut adalah ukuran pertama kali matang gonad (Lm50).…”
Section: Distribusiunclassified